1993
DOI: 10.1007/bf03011317
|View full text |Cite
|
Sign up to set email alerts
|

Does hypothermia or hyperventilation affect enflurane MAC reduction following partial cardiopulmonary bypass in dogs?

Abstract: This study in dogs determined the effect of systemic cooling and arterial hypocarbia during cardiopulmonary bypass (CPB) on the requirements for enflurane anaesthesia (MAC) before and after CPB. Twelve mongrel dogs were each anaesthetized with enflurane in oxygen on (MAC 3 and MAC 4). Dogs were randomly assigned according to PaC02 management during CPB (low, 17.6 5: 8.6 mmHg vs high, 38.9 + 11.5 mmHg) (has,17,6 + 8,6 mmHg vs haut, 38,9 • 11,5 mmHg)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is possible that some of our findings might be attributable to hypoglycaemia or hyperglycaemia, a5 We consider the possibility of hypoglycaemia to be remote given that all animals were healthy and the development of hyperglycaemia to the extent required to alter MAC seems unlikely given the nature of the surgery and our previous experience with the model in which the animals were allowed to recover without apparent neurological sequelae. 7 In summary, we have demonstrated that MAC reduction following CPB is independent of the volatile agent used (enflurane vs isoflurane), type of oxygenator employed (membrane vs bubble), or presence or absence of an in-hne arterial filter in the bypass circuit. The aetiology for the reduction in anaesthetic requirements following CPB remains unknown but the theory that it is related to microembolisation appears less likely.…”
Section: Study Limitationsmentioning
confidence: 73%
See 1 more Smart Citation
“…It is possible that some of our findings might be attributable to hypoglycaemia or hyperglycaemia, a5 We consider the possibility of hypoglycaemia to be remote given that all animals were healthy and the development of hyperglycaemia to the extent required to alter MAC seems unlikely given the nature of the surgery and our previous experience with the model in which the animals were allowed to recover without apparent neurological sequelae. 7 In summary, we have demonstrated that MAC reduction following CPB is independent of the volatile agent used (enflurane vs isoflurane), type of oxygenator employed (membrane vs bubble), or presence or absence of an in-hne arterial filter in the bypass circuit. The aetiology for the reduction in anaesthetic requirements following CPB remains unknown but the theory that it is related to microembolisation appears less likely.…”
Section: Study Limitationsmentioning
confidence: 73%
“…5'6 However, we could not find an independent effect of hypothermia and, in addition, the degree of MAC reduction post-CPB was unaffected by manipulation of arterial carbon dioxide tension (factors known to affect cerebral blood flow and thus delivery of microemboli). 7 To clarify further what factors affect changes in anaesthetic requirements post-CPB, this investigation sought to examine the role that volatile anaesthetic agents might play, and to determine the effect of strategies designed to prevent microemboli released during CPB from reaching the cerebral circulation (membrane oxygenator and presence of an in-line arterial filter), in altering MAC post-CPB. Our hypothesis was that there would be no difference in the degree of MAC reduction following CPB employing enflurane or isoflurane anaesthesia, and that the use of a membrane oxygenator and of an in-line arterial filter would lessen the impact of CPB on reduction of MAC.…”
mentioning
confidence: 99%
“…169 Data in dogs suggests that, independent of any pharmacokinetic changes, there may also be pharmacodynamic changes in drug effect. 165,168 Taken together, the most rational way to administer drugs, particularly infusions, following cardiopulmonary bypass is to titrate the drug to a desired effect. This may be guided by target plasma concentrations 169 but will likely require adjustment (usually a reduction) as the drug's effect becomes manifest.…”
Section: Pharmacomneticsmentioning
confidence: 99%